Examining the link between health measures, management practices and establishment performance - Sandra Broszeit; Marie-Christine Laible (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2017)
We examine the relationship between establishment-level health measures, Anglo-Saxon management practices and labor productivity, as well as median wages. Based on the observation that management practices are positively associated with establishment outcomes, we test whether health measures have a distinct effect on their own, or if they are already comprised in management practices. Using representative survey data from the German Management and Organizational Practices Survey, we find a strong increase in the use of health measures from 2008 to 2013, predominantly in large establishments. Fixed effects regressions confirm that management practices significantly increase labor productivity, however, health measures do not. The reverse is true for median wages, such that health measures are positively associated with median wages, but management practices are not. – – Wir untersuchen den Zusammenhang zwischen betrieblichen Gesundheitsmaßnahmen, Managementpraktiken und Arbeitsproduktivität, sowie Medianlöhnen. Aus der bisherigen Forschung ist bekannt, dass Managementpraktiken in einer positiven Beziehung zu betrieblichen Erfolgsfaktoren stehen. Daher beleuchten wir, ob betriebliche Gesundheitsmaßnahmen, unabhängig von traditionelleren Managementpraktiken, einen Einfluss auf Arbeitsproduktivität und Medianlöhne haben. Repräsentative Befragungsdaten des "Management and Organizational Practices Survey" zeigen einen Anstieg in der Nutzung von betrieblichen Gesundheitsmaßnahmen zwischen den Jahren 2008 und 2013, insbesondere in großen Betrieben. Während Managementpraktiken in einer positiven Beziehung zur Arbeitsproduktivität stehen, haben sie keinen Einfluss auf Medianlöhne. Bei Gesundheitsmaßnahmen lässt sich ein anderes Muster erkennen, sodass diese in keinem Zusammenhang mit der Arbeitsproduktivität stehen, jedoch einen positiven Zusammenhang mit Medianlöhnen aufweisen.
Keywords: D22; I15; J24; L2; M2; 330; management practices; health measures; establishment performance; labor productivity; median wages; linked survey-administrative data; establishments